ANALISIS MINAT MASYARAKAT MENGGUNAKAN APLIKASI HALO DOC DIMASA PANDEMI COVID-19 - Serliyana Cindi Rosita (Bajang Institute, 2022)
The COVID-19 pandemic has had a considerable effect on the health sector, especially on health services. Restrictions on community activities outside the home are encouraged to deal with the spread of the COVID-19 virus. The use of health technology is currently being used as a solution for online health management, one of the applications used is Halodoc. This study aims to determine the effect of security, trust and convenience on public interest in using the Halodoc application during the COVID-19 pandemic. The measuring instrument used is a questionnaire distributed to the community using the Halodoc application in the Surakarta area, the sampling technique using purposive sampling and the Lemeshow equation so that a sample of 100 respondents is obtained. The analytical method used is multiple linear regression analysis.The results of this study indicate that the security variable partially has a significant positive effect on interest with (p-value = 0.041) and a coefficient value of (0.185). The confidence variable partially has a significant positive effect on interest (p-value = 0.032) and the coefficient value is (0.220). The convenience variable partially has a significant positive effect on interest (p-value = 0.007) and the coefficient value is (0.368). Simultaneously, the security, trust and convenience variables have a significant influence on people's interest in using the Halodoc application (p-value < 0.001) with the contribution of the three variables being 62.5%.